Surface-Supported Metal-Organic Framework as Low-Dielectric-Constant Thin Films for Novel Hybrid Electronics - da Silva, Ricardo M. L. [UNESP]; Albano, Luiz G. S.; Vello, Tatiana P.; de Araújo, Wagner W. R.; de Camargo, Davi H. S.; Palermo, Leirson D.; Corrêa, Cátia C.; Wöll, Christof; Bufon, Carlos C. B. [UNESP] (Wiley, 2022)
The miniaturization of electronic devices highlights the need for robust low-κ materials as an alternative to prevent losses in the performance of integrated circuits. For it, surface-supported metal-organic frameworks (SURMOFs), a class of porous-hybrid materials, may cover such a demand. However, the high-intrinsic porosity makes determining the dielectric properties difficult and promotes the integration of SURMOF thin films. Here, the integration of ultrathin HKUST-1 SURMOF films into a 3D functional device architecture using soft-top electrical contacts is addressed. In this novel approach, the device structure assumes an ultracompact capacitor structure allowing determine the dielectric properties of porous thin films with considerable accuracy. A low-κ value of 2.0 ± 0.5 and robust breakdown strength of 2.8 MV cm−1 are obtained for films below 80 nm. The spontaneous self-encapsulated structure provides a footprint-area reduction of up to 90% and yields good protection for the SURMOF toward different hazardous exposure. Finite-element calculations compare the HKUST-1 performance as dielectric layer with well-established insulators applied in electronics (SiO2 and Al2O3). The possibility of integration and miniaturization of HKUST-1, combined with their interesting insulating properties, place this hybrid material as a robust low-k dielectric for novel electronics.
Keywords: dielectrics; HKUST-1; low-κ; metal-organic frameworks; SURMOFs